Titling Practices and Their Implications in Communication Research 1970-2010: Cutesy Cues Carry Citation Consequences1. (July 2022) - Keating, David M.; Richards, Adam S.; Palomares, Nicholas A.; Banas, John A.; Joyce, Nick; Rains, Stephen A.
In order to better understand the state, evolution, and impact of titling practices in the field of communication, we examine the prevalence of stylistic cues in journal article titles and whether such cues predict subsequent citations. We employed a stratified random sample of articles published in 22 communication journals between 1970 and 2010 ( N = 2, 400). Although authors have increasingly used stylistic cues in academic titles, articles with titles containing such cues were cited less frequently. Journal impact modified this relationship: The presence of a stylistic title was associated with more citations if the article was published in a lower impact journal, but fewer citations if it was published in a higher impact journal. Taken together, the results highlight a tension between authors' attempts to distinguish their work in an increasingly crowded marketplace and readers' general reluctance to cite scholarship containing stylistic title cues.